Image of the Month: High Pressure Distal Colostogram in a Patient with an Anorectal Malformation - Apte, Anisha; Brisighelli, Giulia; McKenna, Elise; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2020)
An adequately performed high pressure distal colostogram is crucial to plan surgery in male patients born with anorectal malformations. We present two male patients that underwent a divided sigmoid colostomy with distal mucus fistula in the neonatal period and at 6 months of age underwent a high pressure distal colostogram. In the discussion, we will give some tricks beyond the known rules: how to correctly interpret a high pressure distal colostogram, how to identify the level of a recto-urinary fistula, and how to accurately plan the surgical approach.
Keywords: high pressure distal colostogram; anorectal malformation; recto-urinary fistula